VCO DEVELOPMENT USING 130nm CMOS TECHNOLOGY - A/L Arulnathan, Jonathan (Universiti Teknologi PETRONAS, 2018)
This dissertation focuses on the simulation of a VCO that is optimized for its phase noise properties by utilizing Cadence tools. Besides, a detailed study on the main causes of phase noise in a VCO and techniques of improving the VCO’s phase noise was also conducted in the midst of VCO design.